Botulinumtoxin bei chronischer Epicondylitis humeroradialis - Grüner, Stephan; Schulz, Axel; Schlüter-Brust, Klaus; Lippert-Grüner, Marcela (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Lateral epicondylitis is a common disease in orthopaedic practice. Although the majority of cases do not become chronic, patients who do not respond to the initial treatment may suffer from pain in the long term and effective treatment is challenging. The off-label use of botulinum toxin is one of the common potential indications for the substance in orthopaedics and traumatology. In a literature review of 2000 - 2019, eight EBM ≥ level 3 studies evaluating the use of botulinum toxin in lateral epicondylitis were found. Five of these studies evaluated botulinum toxin versus placebo in chronic cases; two other studies compared botulinum toxin with corticosteroids in acute cases and classic Hohmann surgery in chronic cases; the eighth study compared botulinum toxin in two different injection sites and corticosteroids by classic injection. Our findings suggest that the use of this substance may be a treatment option in refractory chronic cases before surgery is indicated. The working group on botulinum toxin in O & T of the International Musculoskeletal Pain Society (IMPS/IGOST) introduced an alternative injection schedule, which combines findings from the recent clinical literature with practical experience in order to reduce the risk of side effects while ensuring treatment effectiveness. Using 2 simple tests of function and, if necessary, sonographic verification, 2 separate injection sites in the extensor carpi radialis or the extensor digitorum can be identified by palpation. The tendon level on the lateral epicondyle acts as the third injection site. With optimal use of the ampoule content, the 3 injection sites can be infiltrated individually, depending on the muscle status. On the one hand, this enables treatment to take place after a dual therapy approach and, on the other hand, the risk of overdose in a muscle with subsequent unnecessary muscle weakening can be reduced.
Keywords: šlachy; bolest; Tennis Elbow; Pain; botulotoxiny typu A; Pain Measurement; Botulinum Toxins, Type A; Humans; výsledek terapie; tenisový loket; lidé; Tendons; Treatment Outcome; měření bolesti